Ecnometrics : theoretical foundations and empirial perspectives - Nachane, Dilip M. (New Delhi, 2006)
This important new textbook written especially for Indian students, researchers, and teachers comprehensively covers both the theory and the applications aspects of econometrics. It presents a balanced approach to the subject in which the 'how' and 'why'-techniques and programmes as well as empirical illustrations-share an equal emphasis. This book has been developed as a self contained text and assumes only a basic knowledge of algebra and calculus. Its coverage includes: Foundations of Probability and Related Statistical Concepts Classical Inference Linear Regression Models Time Series Models (including VARs and Spectral Analysis) Dynamic Econometric Models (causality, exogeneity, unit roots, and co-integration)
Keywords: Mathematical economics